Gestão estratégica da criação do conhecimento nas organizações hospitalares: um estudo baseado na construção de protocolos médico-assistenciais - Jacques, Jacques Édison (Universidade do Vale do Rio do Sinos, 2007)
This study is embedded in the field of organizational strategies because of the approach adopted to investigate the management of knowledge creation. Health care services are faced with the constant need to incorporate knowledge because of the development of new technologies in the form of both innovative resources and health care models. Such conditions demand a systematic process of strategic and operational learning. However, organizational contexts interfere with management processes. Hospitals have been increasingly interested in using health care protocols as management tools because protocols incorporate new knowledge into diagnostic and therapeutic procedures. Therefore, this study investigated, by means of protocols developed by multidisciplinary teams, how the creation of a learning environment affected management capabilities and determined the strategic content of knowledge generated to support the sustainability of hospital organization. This qualitative, multiple-case study was carried out in tw
Keywords: gestão do conhecimento; organizações hospitalares; protocolos médico-assistenciais; estratégias organizacionais; Ciências Sociais Aplicadas